SOFT TISSUE CYSTS IN CHILDREN’S MAXILLOFACIAL AREA AND NECK - Ткаченко, П.І.; Білоконь, С.О.; Старченко, І.І.; Гуржій, О.В.; Belokon, N.; Литвин, А.О. (World of Medicine and Biology, 2016)
Microscopic studies have shown that the wall of epidermoid cycts had a small connective tissue capsule, the thickness of which was quite variable depending on the size of the formation, terms of existence, occurrence of inflammation in the medical history, the patient's age and a number of individual features. The internal surface of the capsule was lined with multilayer pavement epithelium, structurally resembling the epidermis of the skin:, i.e., all the layers were observed, and in the cavity of the cysts keratinous masses were detected. However, the thickness of the epithelial lining was usually considerably less than the thickness of the original epidermis of the skin due to reducing of number of series of Malpighian layer and the sizes of each cell.All patients with soft tissue cysts in the maxillofacial area underwent extirpation of the formations.
Keywords: children; soft tissue cysts; maxillofacial area.